Building Paper arrives in New Zealand - Isaacs, Nigel (Architectural History Aotearoa, 2023)
Building paper, invented in Beloit, Wisconsin in 1869, arrived in New Zealand in the late 1880s. In 1891 it was used under the corrugated iron roof and walls in the four-bed Tasman Glacier Hut where it would have provided relief from condensation on the inside of the corrugated iron as well as reducing the ability of the wind to blow through the hut. Building paper quickly became common place, with advertising from English and American manufacturers appearing daily newspapers as well as trade journals. The paper traces the first decades of building paper use in New Zealand as it evolved from a novelty to a common building product – hidden under the cladding but improving on the comfort of the occupants. It ends with a brief foray into the twentieth century, with examples of its use and eventual inclusion in building controls starting with NZSS 95 Part IX: Light Timber Construction:1944.